2015
DOI: 10.1016/j.bbmt.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Short Course of Post-Transplantation Cyclophosphamide and Bortezomib for Graft-versus-Host Disease Prevention after Allogeneic Peripheral Blood Stem Cell Transplantation Is Feasible and Yields Favorable Results: A Phase I Study

Abstract: An effective graft-versus-host disease (GVHD) preventative approach that preserves the graft-versus-tumor effect after allogeneic hematopoietic stem cell transplantation (HSCT) remains elusive. Standard GVHD prophylactic regimens suppress T cells indiscriminately and are suboptimal. Conversely, post-transplantation high-dose cyclophosphamide selectively destroys proliferating alloreactive T cells, allows the expansion of regulatory T cells, and induces long-lasting clonal deletion of intrathymic antihost T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Further studies aim to more clearly define the optimal patient population, conditioning intensity, and graft source of post-transplant cyclophosphamide for GVHD prevention, including investigating its use in combination with cyclosporine after myeloablative conditioning (NCT01427881) or with tacrolimus-MMF after myeloablative or reduced-intensity conditioning (NCT01010217). One recent trial also demonstrated that post-transplantation cyclophosphamide and bortezomib were feasible and may be effective GVHD prophylaxis after reduced-intensity transplantation from matched donors [93]. …”
Section: Other Novel Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies aim to more clearly define the optimal patient population, conditioning intensity, and graft source of post-transplant cyclophosphamide for GVHD prevention, including investigating its use in combination with cyclosporine after myeloablative conditioning (NCT01427881) or with tacrolimus-MMF after myeloablative or reduced-intensity conditioning (NCT01010217). One recent trial also demonstrated that post-transplantation cyclophosphamide and bortezomib were feasible and may be effective GVHD prophylaxis after reduced-intensity transplantation from matched donors [93]. …”
Section: Other Novel Strategiesmentioning
confidence: 99%
“…A randomized phase II trial of bortezomib combined with either tacrolimus-methotrexate or tacrolimus-sirolimus compared with tacrolimus-methotrexate in this patient population is underway (NCT01754389). A recent phase I study also reported that bortezomib in combination with high-dose cyclophosphamide after HCT from matched siblings or unrelated donors after reduced-intensity conditioning was safe and resulted in encouraging levels of acute GVHD that merit further evaluation [93]. …”
Section: Other Novel Strategiesmentioning
confidence: 99%
“…An immunomodulatory effect of bortezomib has also been suggested in the allogeneic HCT setting, based on the observation of decreased incidence of graft-versus-host disease when patients receive bortezomib after transplantation. 22,23 Our data demonstrate that combined bortezomib and temsirolimus had activity in patients with heavily pretreated NHL, with manageable toxicities. This combination could be explored further in the future by adding additional agents to the regimen or by replacing bortezomib with newer proteasome inhibitors, such as carfilzomib or ixazomib.…”
Section: Discussionmentioning
confidence: 68%
“…This observation suggests that temsirolimus/bortezomib may have created an immunomodulatory/antilymphoma effect that persisted even after the completion of protocol therapy. An immunomodulatory effect of bortezomib has also been suggested in the allogeneic HCT setting, based on the observation of decreased incidence of graft‐versus‐host disease when patients receive bortezomib after transplantation …”
Section: Discussionmentioning
confidence: 99%
“…However, unfavorable rates of acute GVHD have been reported when PTC is used alone, in particular in the setting of reduced-intensity conditioning and peripheral blood grafts [16]. This has prompted several investigators to examine the role of PTC in combination with cyclosporine [21], sirolimus [22,23], or bortezomib [24].…”
Section: Discussionmentioning
confidence: 99%